Optimalisasi Pengelolaan Sampah dan Daur Ulang untuk Mengurangi Emisi Gas Rumah Kaca Di Perkotaan - Husna, Fitriati; Windu Fajar Arum; Evi Aryanti; Islamul Hadi (Lamda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2025)
Waste management with the old paradigm (collection, transportation, disposal) causes waste to be concentrated in landfills in large quantities (Tchobanoglous et al., 1993). Waste that ends up in landfills will undergo a decomposition process and cause emissions of one of the GHGs, namely methane gas (CH4). This gas causes an effect 20-30 times greater than carbon dioxide gas (CO2) (Damanhuri, E., & Padmi, T., 2015. Effective waste management in urban areas poses a major challenge in reducing greenhouse gas (GHG) emissions and ensuring environmental sustainability. This research analyzes the optimization of waste management and recycling as a strategy to lower GHG emissions in several major cities in Indonesia. A qualitative approach was employed, utilizing surveys and interviews with stakeholders, including government, waste managers, and community members. The findings indicate that an integrated management system, accompanied by educational programs and incentives for community participation, can enhance recycling rates and reduce waste volume. The reduction in GHG emissions positively correlates with decreased poorly managed waste and increased use of recycled materials. This study emphasizes the importance of collaboration among government, community, and private sectors in creating sustainable management systems, while recommending policies to raise awareness and improve urban waste management infrastructure, ultimately supporting the conservation of natural resources.